2017
DOI: 10.1080/23288604.2017.1342179
|View full text |Cite
|
Sign up to set email alerts
|

The Implications of Aging on the Health Systems of the Pacific Islands: Challenges and Opportunities

Abstract: Abstract-Population aging presents substantial and unique challenges and opportunities to Pacific Island countries. The countries in this region currently have young populations, but the population is rapidly changing. With some of the highest rates of obesity and diabetes in the world, an aging population will-unless urgent action is taken-put additional pressure on all aspects of the health system: leadership and governance; health financing; health workforce, service delivery; drugs and equipment; and infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Although there are other frameworks proposed to assess health systems, they usually look at overall performance, missing some important details regarding the allocation of resources and inequalities between different population groups within a country [15,40]. On the other hand, there is a vast literature on the need to adapt health systems to the challenges of population aging [41][42][43][44]. However, these articles usually advocate for a reform rather than presenting the rationale for changing; they use the system's perspective instead of a beneficiaries' approach [45].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are other frameworks proposed to assess health systems, they usually look at overall performance, missing some important details regarding the allocation of resources and inequalities between different population groups within a country [15,40]. On the other hand, there is a vast literature on the need to adapt health systems to the challenges of population aging [41][42][43][44]. However, these articles usually advocate for a reform rather than presenting the rationale for changing; they use the system's perspective instead of a beneficiaries' approach [45].…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining patterns of multimorbidity in people with psychosis and depression in LMICs found that multimorbidity was most evident in younger age groups (Stubbs et al ., 2016; Stubbs et al ., 2017). Congruently, the Pacific region currently has relatively young populations, with over half of countries having a median age of less than 25 years (Anderson and Irava, 2017).…”
Section: Multimorbidity and Mental Disordersmentioning
confidence: 99%
“…The challenge of incorporating NCDs into UHC strategies is illustrated in the case of several countries in the Pacific. 21,22 The median age in these countries is quite low and there is little public awareness of the issues associated with demographic transition. Several countries have very high prevalence of diabetes and other risk factors for cardiovascular disease, but the impact on hospital admissions has been modest.…”
Section: Managing Competing Interestsmentioning
confidence: 99%
“…As the population ages, the demand for hospital care is projected to rise rapidly and analysts emphasize the need to adapt PHC services to support effective management of NCDs before this happens. 22 However, it is easier for governments to respond to immediate problems than to those projected to occur in the future. associated with rapid rises in expenditure.…”
Section: Managing Competing Interestsmentioning
confidence: 99%